Aerodynamic design of transport aircraft - Obert, Ed (Ios Press ; Delft University of Technology, Faculty of Aerospace Engineering, Section Design of Aircraft and Rotorcraft, 2009)
After the demise of Fokker in 1996 one feared that interest in aeronautical engineering would strongly diminish. Two years later the situation was re-appraised, and the interest in aeronautical engineering remained, so the course was reinstated. This title includes the author's lecture notes from these courses.